CHARACTERIZATION OF THE HUMAN HEPATOCELLULAR CARCINOMA (HEPG2) CELL LINE AS AN IN VITRO MODEL FOR CADMIUM TOXICITY STUDIES - DEHN, P. F; WHITE, C. M; CONNERS, D. E; SHIPKEY, G; CUMBO, T. A (In vitro cellular & developmental biology. Animal, 2004)
Biochemical indicators and in vitro models, if they mimic in vivo responses, offer potentially sensitive tools for inclusion in toxicity assessment programs. The purpose of this study was to determine whether the HepG2 cell line would mimic known in vivo or in vitro (or both) responses of mammalian systems when confronted with cadmium (Cd2+). Uptake and compartmentalization of Cd2+, metallothionein (MT) compartmentalization, and glutathione (GSH) depletion were examined. In addition, several cytotoxic and stress effects, e.g., viability (neutral red [NR] uptake, 3-[4,5-dimethylthiozole-2-yl]-2,5,-biphenyl tetrazolium bromide [MTT] dye conversion, and live/dead [L/D]), membrane damage (lactate dehydrogenase leakage), metabolic activity (adenosine triphosphate levels), and detoxification capabilities (GSH content, cytochrome P4501A1/2 [EROD (ethoxyresorufin-o-deethylase)] activity, and MT induction), were measured in both naive (no previous exposure) and Cd2+ preexposed cells. Cadmium uptake increased during a 24-h period. Metallothionein induction occurred in response to both Cd2+ and ZnCl2; however, Cd2+ was the more potent inducer. Both Cd2+ and MT were localized primarily in the cytoplasmic compartment. All biochemical responses, except EROD, showed concentration– response relationships, after 24-h exposure to Cd2+ (ranges 0–3 ppm [26.7 μM]). Cadmium effects were reduced in preexposed cells, indicating adaptive tolerance or increased resistance had occurred. Twenty-four–hour LC50, dose causing death of 50% of the test subjects, values were 0.97, 0.69, and 0.80 ppm (8.7, 6.2, and 7.2 μM) for naive cells and 1.45, 1.21, and 1.39 ppm (12.9, 10.7, and 12.3 μM) for preexposed cells based on the NR, MTT, and L/D assays, respectively. These data indicate that this carcinoma cell line is a useful in vitro model for cadmium toxicity studies.